Correlation Between Vocabulary Mastery and Fluency in Speaking at Universitas Tanjungpura - Diyas Herdian Putra; Ikhsanudin Ikhsanudin; Eusabinus Bunau (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2021)
This research, entitled “Correlation Between Vocabulary Mastery and Fluency in Speaking” was carried out to the fifth semester students of English Education Study Program. The population of this research is fifth semester students of English Education Study Program of Teacher Training and Education Faculty at Tanjungpura University with the sample size of 30. The result of data analysis revealed the correlational between both variable from the samples is showing the correlational coefficient (r) value of 0.19. This value showed vocabulary mastery has low correlation with fluency in speaking. The contribution of vocabulary mastery to fluency in speaking is 3.6% which is almost non-existent. The hypothesis was tested by comparing the r value with r table, with the degree of freedom (df = n-2) of 28 and 1% level of significance. The r value (0.19) is lower than r table (0.463). It means, the alternative hypothesis (Ha) is rejected and null hypothesis (Ho) is accepted. With this research done, students should improve their speaking ability and remember more vocabularies to become a more and better speaker. The writer hopes this research may be beneficial to the readers and might resulting in newer research with different aspect and better concepts.